Exploring Flouted Maxims in Homeless to Harvard: The Liz Murray Story Movie - Sinom, Patrick Adtya Pratama; Bram, Barli (Aksara: Jurnal Bahasa dan Sastra, 2022)
Homeless to Harvard (2003) is an actual event story and a motivational movie of Liz Murray, a woman whose parents are drug addicts. This research was focused on finding the maxims flouted and the reason for flouting the maxims. The study used a qualitative method. To analyse the collected data, descriptive research and pragmatic identity were used. Results showed 12 times maxims were flouted in total. The flouted maxims were quantity (five times or 41%), quality (two or 17%), relation (two or 17%), and manner (three or 25%). Results also revealed the motivation for flouting the maxims and motives for flouting them were collaborative, conflict, and competitive. Since this research was limited to Grice’s cooperative principles and motives in flouting maxims, future researchers are encouraged to investigate more variables, such as implicature, speech acts, and deixis. Keywords: Cooperative principles, flouting maxims, motivational movie